Sex-stratified Correlates of Cyberbullying among Thai Adolescents: Insights from a School-based National Survey during COVID-19 Epidemic - Dadras, Omid (SPRINGER HEIDELBERG, 2025)
Cyberbullying is a significant concern among adolescents, impacting mental health and behavior. This study aimed to examine the sex-specific prevalence and correlates of cyberbullying victimization among Thai adolescents. Data from the 2021 Thailand Global School-based Student Health Survey, involving 5,657 students in grades 7-12, were analyzed. Cyberbullying victimization was assessed through self-reported experiences in the past 12 months. Twenty-three outcome variables across five domains (lifestyle, mental health, substance use, sexual behaviors, and violence) were examined. Logistic regression models, adjusted for age, assessed the associations between cyberbullying and these outcomes separately for males and females, accounting for the complex survey design and sampling weights. Approximately 17% of male and 13% of female students experienced cyberbullying in the past year. For males, cyberbullying was significantly associated with negative outcomes, including poor mental health (loneliness, insomnia due to anxiety, suicidal thoughts and attempts), increased substance use (cigarettes, alcohol, marijuana), and risky sexual behaviors (multiple sexual partners). Male victims were also more likely to engage in violent behaviors and experience physical attacks. For females, cyberbullying was linked to poor lifestyle choices (sedentary lifestyle, poor oral hygiene, inadequate fruit/vegetable intake), heightened mental health issues (loneliness, insomnia, suicidal thoughts and attempts), and substance use. Female victims were also at higher risk of experiencing violence and traditional bullying. This study documented high cyberbullying rates among Thai adolescents and calls for comprehensive mental-health support, especially for males with elevated suicidal ideation; healthy-lifestyle and social-connectedness programs for females; and universal resilience and digital-citizenship training for all youth.